(3GdCfUGa aj GdGfJUGa dCgd GdMb ef Cgd GdESQGas - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3ajLH Ydi cd YGbd Cf jYJbO Gdjhe hjYed eG jfLjg hjfaYg ZOGU s
(3BNQgG (B:s
(3hCfJ JYde CjgG GdYGbd Cf GdMb dGjchf GdG ai LgI hMOI dG ZjQ hdG jecf Cf jchf ai LHgJjf eNJdaJjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B- (3cdjI Mbhb (B(130 - (3L(B) s
Keywords: (3GdJhMjO hGdedd hGdfMds